The Macroeconomic Consequences of Terrorism - S. Brock Blomberg; Gregory D. Hess; Athanasios Orphanides (Center for Economic Studies and ifo Institute (CESifo), 2004)
We perform an empirical investigation of the macroeconomic consequences of international terrorism and interactions with alternative forms of collective violence. Our analysis is based on a rich unbalanced panel data set with annual observations on 177 countries from 1968 to 2000, which brings together information from the Penn World Table dataset, the ITERATE dataset for terrorist events, and datasets of external and internal conflict. We explore these data with cross-sectional and panel growth regression analysis and a structural VAR model. We find that, on average, the incidence of terrorism may have an economically significant negative effect on growth, albeit one that is considerably smaller and less persistent than that associated with either external wars or internal conflict. As well, terrorism is associated with a redirection of economic activity away from investment spending and towards government spending. However, our investigation also suggests important differences both regarding the incidence and the economic consequences of terrorism among different sets of countries. In OECD economies, in particular, terrorist incidents are considerably more frequent than in other nations, but the negative influence of these incidents on growth is smaller.
Keywords: 330; growth; conflict; terrorism